The Influence of Green Innovation and Environmental Responsibility on Company Value in the Consumer Goods Industry Sector Listed on the Indonesia Stock Exchange for the Period 2020 – 2023 - Sitanggang, David Patar; Simanjuntak, Arthur; Ginting, Mitha Christina; Elisabeth, Duma Megaria (Basic and Applied Accounting Research Journal, 2025)
This research examines the relationship between green innovation and environmental responsibility on company valuation across 12 purposively selected consumer sector businesses from 51 companies listed on the IDX (2020-2023). Through multiple linear regression using SPSS 26, the findings reveal that individually both variables have a significant negative impact on company value, while simultaneously demonstrating a significant influence. The coefficient of determination indicates the research model explains 19.7% of variations in company value, with 80.3% influenced by external factors. These findings present a new perspective on the complex relationship between sustainable practices and market perceptions of company value in the Indonesian consumer industry context, which differs from conventional stakeholder expectations.